Knowledge and Perception of Forest Conservation in the Forestry Department Headquarters of Peninsular Malaysia - Abdul Fuad, Ahmad Farid (2001)
The study was carried out to determine the extent of knowledge and the perception the staff have on forest conservation concepts and issues. A total of 57 respondents comprising of forest officers and administrative officers attached to all units within the Forestry Department Headquarters of Peninsular Malaysia participated in the study. The questionnaire was designed in three parts; Part I requested the respondents' demographic information, meanwhile the other two parts consist of 17 statements to test the knowledge of the staffs on the theory and concepts of forest conservation stipulated in current conservation biology textbooks and manifested within the National Policy on Biological Diversity 1998, and 20 statements to assess their perception on the current issues regarding forest conservation in Malaysia. The results showed that the respondents, regardless of their position have fair knowledge and considerably perceived positively the forest conservation concepts and issues. The results of Spearman rank order correlation test showed that only academic level positively correlated with knowledge. Profession or job specialisation was negatively correlated with perception. There was significant correlation in knowledge and perception of the respondents.